Corry Van Stenus, Perempuan dalam Perjuangan Abdul Qahhar Mudzakkar 1950-1965 - Azizah, Nurul (Rihlah: Jurnal Sejarah dan Kebudayaan, 2020)
Rebellion is often identified as a masculine realm, which is dominated by men. But in the case of Kahar Mudzakkar’s rebellion in South Sulawesi, we could find a women named, Corry Van Stenus,. she was a Javanese-Dutch German and also the second wife of Kahar Mudzakkar. This paper focuses on Corry’s life during the Kahar Mudzakkar rebellion. This theme is rarely discussed because the writings on rebellion are dominated by men. By using the historical approach, this paper wants to show about women in rebellion. in this case, Corry and her role as a woman, wife and mother in a rebellion. In conclusion, Corry became a woman who played a role in Kahar Mudzakkar’s rebellion. From the domestic sphere, she became the wife and mother who accompanied her husband in rebellion. From the political realm, she became a lead of the Sulawesi Islamic Women’s Movement (GERWAIS).